Toward Defining Healthcare Simulation Escape Rooms. (February 2021) - Anderson, Mindi; Lioce, Lori; M. Robertson, Jamie; O. Lopreiato, Joseph; A. Díaz, Desiree
Background: Escape rooms have been adapted from a range of educational purposes across disciplines, including healthcare simulation. The use of this technique has become increasingly popular among industry and faculty members. We sought to clarify the characteristics ofhealthcare simulation escape rooms in order to work toward a shared mental model anddefinition . Methods: A scoping review of the literature with an environmental scan of websites and other public information was performed to identify concepts which describe educational and healthcare simulation escape rooms to differentiate between and determine key features and scope of this clinical education tool to provide an interprofessional definition. Twenty-three references were used. Results: Healthcare simulation escape rooms share many of the characteristics of those being used for education and may be utilized for teaching a variety of skills. These may be conducted either within a simulation scenario, within the simulation/simulated environment, and/or with associated equipment. It is essential that the development and implementation of these escape rooms follow design standards of best practice for healthcare simulation for optimal learning. Only one definition of simulation escape rooms was found. Discussion: While similar to escape rooms utilized in other forms of education, there are principal differences between those escape rooms and ones used in healthcare simulation. Key features include utilization of core healthcare simulation principles, including providing a safe and realistic learning environment. Conclusion: Escape rooms may be used to engage learners in a simulation experience. It is important to differentiate between true simulation escape rooms and escape rooms that do not reflect healthcare simulation-based learning experiences. An expanded definition is provided, as reflected by the literature review, to provide a clearer understanding of the term as applied to healthcare simulation and enhance repeatable studies to advance the science of healthcare simulation.